ANALISIS MENGATASI PENURUNAN HARGA TANDAN BUAH SEGAR (TBS) KELAPA SAWIT PETANI SWADAYA DI INDONESIA - Syahril Syahril; Irmayani Irmayani (Universitas Teuku Umar, 2019)
Research aims to look for formulations how to overcome the price reduction of fresh fruit bunches (TBS) in Indonesia along with the movement of CPO Price in the international market so that smallholders and palm oil entrepreneurs can keep Revenue stability in its business sustainability. This research uses qualitative methods with descriptive analysis. The result of research obtained is the lack of demand (demand) that led to the accumulation of CPO (supply) in palm oil Mills (MCC). The accumulation of crude palm oil (CPO) becomes among the company's alibi as a justification for buying cheap prices of fresh fruit bunches (TBS) farmer oil palm. The instability of the European and United States economies, along with the time of harvest crops of other vegetable oil products, such AS sunflower, soy, and corn, encourages the decline in the price of CPO exports. The solution to overcome TBS price decline is to build the downstream CPO industry, the establishment of TBS Pengumpus cooperative and diversify by expanding the type of agricultural activities and multiply the type of crops on a land. Keywords: TBS price drop, CPO export price, formulation solution.